A 62-kD protein required for mitotic progression is associated with the mitotic apparatus during M-phase and with the nucleus during interphase (The Rockefeller University Press, 1992)
A protein of 62 kD is a substrate of a calcium/calmodulin-dependent protein kinase, and both proteins copurify with isolated mitotic apparatuses (Dinsmore, J. H., and R. D. Sloboda. 1988. Cell. 53:769- 780). Phosphorylation of the 62-kD protein increases after fertilization; maximum incorporation of phosphate occurs during late metaphase and anaphase and correlates directly with microtubule disassembly as determined by in vitro experiments with isolated mitotic apparatuses. Because 62-kD protein phosphorylation occurs in a pattern similar to the accumulation of the mitotic cyclin proteins, experiments were performed to determine the relationship between cyclin and the 62- kD protein. Continuous labeling of marine embryos with [35S]methionine, as well as immunoblots of marine embryo proteins using specific antibodies, were used to identify both cyclin and the 62-kD protein. These results clearly demonstrate that the 62-kD protein is distinct from cyclin and, unlike cyclin, is a constant member of the cellular protein pool during the first two cell cycles in sea urchin and surf clam embryos. Similar results were obtained using immunofluorescence microscopy of intact eggs and embryos. In addition, immunogold electron microscopy reveals that the 62-kD protein associates with the microtubules of the mitotic apparatus in dividing cells. Interestingly, the protein changes its subcellular distribution with respect to microtubules during the cell cycle. Specifically, during mitosis the 62- kD protein associates with the mitotic apparatus; before nuclear envelope breakdown, however, the 62-kD protein is confined to the nucleus. After anaphase, the 62-kD protein returns to the nucleus, where it resides until nuclear envelope disassembly of the next cell cycle.